Criminal Careers of Individuals Convicted for a Sexual Offence: an International Comparison - Robert, Luc (Journal of developmental and life-course criminology, 2023)
By comparing criminal careers of individuals who have sexually offended to those who have not sexually offended, the current study examines whether their criminal career parameters and trajectories differ. National conviction records (entire criminal history and about 18 years of follow-up after index offence) from Belgium and the Netherlands are used to describe and compare the criminal careers of individuals involved in sexual or non-sexual offending. Group-based trajectory models are estimated for each offender class per country. The results show no substantive differences between individuals convicted for sexual offences and individuals convicted for non-sexual offences on age of onset and termination, duration, frequency, and crime mix. Group-based trajectory modeling results in a four-group model with a low-level offending (± 65%), late onset offending (± 12.5%), adolescent and young adult offending (± 17.5%), and persistent offending (± 5%) group. Trajectory patterns are similar across offender class and between countries. ANOVA comparisons between trajectory groups show few differences in criminal career parameters and many similarities. Only small differences could be established between criminal careers of persons convicted for sexual offences and those convicted for non-sexual offences. This leads us to question assumptions about persons convicted for sexual offences as offenders with unique trajectories.